Totally Laparoscopic Repair of an Ileal and Uterine Iatrogenic Perforation Secondary to Endometrial Curettage - Vecchio, Rosario (Int Surg, 2015)
Small bowel perforation is a unique, serious complication during endometrial biopsy. The authors report a case of a double uterine-ileal perforation totally managed by primary laparoscopic repair. A 63-year-old female was admitted with acute abdomen 2 days after an endometrial curettage. Abdominal X-ray shows signs of pneumoperitoneum. Emergency diagnostic laparoscopy was performed and a uterine-ileal perforation was identified. Repair was accomplished by a totally laparoscopic intracorporeally suturing of the 2 breaches. Postoperative course showed only a delayed ileus and the patient was discharged after 5 days with no complications. When acute abdomen arises following uterine biopsy, a potential iatrogenic intestinal laceration always has to be ruled out. Laparoscopic approach is a quick and safe technique in these cases. Totally laparoscopic primary closure of the iatrogenic ileal laceration may be accomplished with low morbidity.